Simulation of platelet adhesion and aggregation regulated by fibrinogen and von Willebrand factor - Mori, Daisuke; Yano, Koichiro; Tsubota, Ken-ichi; Ishikawa, Takuji; Wada, Shigeo; Yamaguchi, Takami (Thrombosis and Haemostasis, 2008)
We propose a method to analyze platelet adhesion and aggregation computationally, taking into account the distinct properties of two plasma proteins, vonWillebrand factor (vWF) and fibrinogen (Fbg). In this method, the hydrodynamic interactions between platelet particles under simple shear flow were simulated using Stokesian dynamics based on the additivity of velocities. The binding force between particles mediated by vWF and Fbg was modeled using the Voigt model. Two Voigt models with different properties were introduced to consider the distinct behaviors of vWF and Fbg. Our results qualitatively agreed with the general observation of a previous in-vitro experiment, thus demonstrating that the significant development of thrombus formation in height requires not only vWF, but also Fbg. This agreement of simulation and experimental results qualitatively validates our model and suggests that consideration of the distinct roles of vWF and Fbg is essential to investigate the physiological and pathophysiological mechanisms of thrombus formation using a computational approach.
Keywords: Computational simulation; glycoprotein receptors; thrombus; shear flow